Dynamic softening of vortex lines in YBa2Cu3O7-δ single crystals - Nieva, Gladys; López, D.; Jagla, E. A.; Righi, E. F.; Osquiguil, E.; Nieva, G.; Morré, E.; de la Cruz, F.; C.A.Balseiro (Elsevier, 1996)
Fil: López, D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina